Identification and proper placement of children with learning disabilities, san perfecto: an assessment - Patangan, Norma R. (Manila: National University, 2007)
This research was limited to the teachers of San Perfecto Elementary School who are at present handling Grades IV, V, VI wherein the referred pupils with learning disabilities are found.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.